Patronage avoidance in James - Kloppenborg, John S. (Hervormde teologiese studies, 1999)
James 2:1-13 takes the form of a rhetorical "elaboration on a theme" described in Ps-Cicero's Rhetorica ad Herennium 2.18.28, and is directed not merely at the abstract issue of partiality or the issue of rich versus poor, but at the practice of patronage and its attendant effects on social interaction. James attacks the practice of patronage and reliance on the stereotypes of patronage as demeaning pseudo-friendship as well as the client, and contrasts this with true friendship from God.